Establishment of DRIS standards and sufficiency range for ‘nanica’ banana trees in Vale do Ribeira - de Oliveira, Cibelle Tamiris; Rozane, Danilo Eduardo [UNESP]; de Deus, José Aridiano Lima; Lima, Juliana Domingues [UNESP]; Lopes, Marcelo Domingos Chamma [UNESP]; de Souza, Wilson José Oliveira [UNESP] (Universidade Estadual de Maringa, 2024)
For a banana tree to reach its productive potential, plants must be nutritionally balanced. Therefore, it is important to use methods that diagnose the nutritional status of plants through chemical leaf analysis, considering the relationships between nutrients and taking advantage of productivity and nutritional monitoring data from orchards. This study aimed to establish norms and ranges of nutrient sufficiency for ‘Nanica’ banana trees in Vale do Ribeira, São Paulo state, using the Diagnosis and Recommendation Integrated System (DRIS) method. Productivity data and chemical analysis of the leaf tissue of 291 commercial plots of Nanica banana trees, collected between 2015 and 2020 in Vale do Ribeira, were used. The DRIS method was used to establish norms and sufficiency ranges for N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn. Fruit yield did not correlate with the average nutritional balance index (NBIa), indicating that its variation was affected by non-nutritional factors. The contents of K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn showed high correlations with their respective nutritional indices. The sufficiency ranges and adequate nutrient contents differed from the values established for bananas in the literature.
Keywords: bivariate method; leaf diagnosis; Musa spp; nutritional balance